Творческая эволюция М. Зощенко (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article investigates the problem of Zoschenko’s creative evolution, conditioned by changes of the author’s attitude to his fiction characters.